Comment on “Healthcare-Seeking Behaviour for Obstetric Complications in Ethiopia: A Multilevel Mixed-Effect Analysis” - Rachana Mehta; Ranjana Sah (Health Services Insights)
This commentary addresses methodological and interpretive limitations in Geremew et al.’s study on healthcare-seeking behaviour for obstetric complications in Ethiopia, emphasizing the need for clinically validated definitions, analytical exploration of variable interactions, inclusion of all obstetric events, and facility-level cross-validation to strengthen the policy relevance and accuracy of the findings.